Application of 3-mercaptopropyltriethoxysilane modified graphene oxide to reduction of AND sensitivity
Through the composite technology of 3-mercaptopropyltriethoxysilane modified graphene oxide and ammonium dinitamide, the high sensitivity and low thermal stability of ADN are solved, and the effects of reducing sensitivity, improving thermal stability and promoting complete decomposition are achieved, and the stability of the propellant formula is improved.
Patent Information
- Application Number
- CN202411886421.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Ammonium dinitamide (ADN) has high impact sensitivity and friction sensitivity, which limits its application and is insufficient thermal stability, affecting the stability of the propellant formula.
Compounded with 3-mercaptopropyltriethoxysilane modified graphene oxide and ammonium dinitamide, and the composite was prepared by mixing and dropping addition of γ-butyrolactone solution to reduce the impact and frictional sensitivity of ADN and improve its thermal stability.
It effectively reduces the impact sensitivity and friction sensitivity of ADN, improves the thermal decomposition temperature and thermal stability, promotes the complete decomposition and full combustion of ADN, and improves the stability of the propellant formula.
Smart Images

Figure BDA0005199418250000071 
Figure BDA0005199418250000081 
Figure HDA0005199418260000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energetic materials, and in particular relates to the application of 3-mercaptopropyltriethoxysilane-modified graphene oxide for reducing AND sensitivity. Background Art
[0002] ADN (chemical name: ammonium dinitramide) is a new type of high-energy green oxidant composed of ammonium cations and dinitramide anions. It has a high density (1.82g / cm 3 ), high oxygen coefficient (2.0), clean fuel gas (halogen-free), etc. Compared with the common oxidant ammonium perchlorate (AP), ADN has a higher formation enthalpy (ADN: -1208kJ / kg, AP: -2782kJ / kg), a smaller average relative molecular mass of fuel gas (ADN: 26, AP: 31), and the theoretical specific impulse of ADN-based solid propellant with the same mass content is 3s to 10s higher than that of AP-based solid propellant. However, its application is limited due to its low sensitivity. Summary of the invention
[0003] In view of the defects or shortcomings of the prior art, the present invention provides an application of 3-mercaptopropyltriethoxysilane modified graphene oxide for reducing the impact sensitivity and friction sensitivity of ammonium dinitramide or / and improving the thermal stability and mass loss of ammonium dinitramide.
[0004] The present invention also provides a method for preparing a 3-mercaptopropyltriethoxysilane-modified graphene oxide / ammonium dinitramide composite, and the provided preparation method comprises the following steps:
[0005] Step 1, at 20-40° C., uniformly mix a γ-butyrolactone solution of 3-mercaptopropyltriethoxysilane-modified graphene oxide and a γ-butyrolactone solution of ADN to obtain a mixed solution;
[0006] Step 2, under the condition of 20-40° C., the mixed solution obtained in step 1 is added dropwise to an organic solvent; after the addition is completed, the precipitate is collected and dried at room temperature to obtain a 3-mercaptopropyltriethoxysilane-modified graphene oxide / ammonium dinitramide complex; the organic solvent is selected from one or a mixture of two or more of dichloromethane, toluene, cyclohexane and chloroform.
[0007] An optional solution is to add graphene oxide to γ-butyrolactone and perform ultrasonic dispersion at a temperature of 20 to 35° C. to obtain a γ-butyrolactone solution of graphene oxide.
[0008] An optional solution is to add ammonium dinitramide to γ-butyrolactone and stir the mixture evenly at a temperature of 20 to 35° C. to obtain a γ-butyrolactone solution of ADN.
[0009] An optional solution is to add the γ-butyrolactone solution of 3-mercaptopropyltriethoxysilane-modified graphene oxide to the γ-butyrolactone solution of ADN, stir at 20-35° C. and then perform ultrasonic dispersion to obtain the mixed solution obtained in step 1.
[0010] An optional scheme is that the usage ratio of 3-mercaptopropyltriethoxysilane modified graphene oxide and γ-butyrolactone in the γ-butyrolactone solution of 3-mercaptopropyltriethoxysilane modified graphene oxide is 0.4mg~40mg:20g~40g; the usage ratio of ADN and γ-butyrolactone in the γ-butyrolactone solution of ADN is 0.3g~2.5g:10g~50g.
[0011] An optional solution is that the amount of organic solvent used is 500g to 1500g.
[0012] The invention discloses a method for preparing a graphene oxide / ammonium dinitramide (ADN) composite which adopts 3-mercaptopropyltriethoxysilane to modify graphene oxide, thereby reducing the impact sensitivity of ammonium dinitramide (ADN), improving the thermal stability of ADN and enhancing the thermal decomposition performance.
[0013] Compared with ADN, the 3-mercaptopropyltriethoxysilane modified graphene oxide / ADN composite of the invention has a spherical solid composite structure and uniform particles; the impact sensitivity is reduced from 9.31 J to 10.0 J to 19.3 J, and the friction sensitivity is reduced from 72% to 20% to 31%; the thermal performance of ADN can also be improved, the thermal decomposition temperature of ADN is delayed by 1.56° C. to 5.06° C., thereby improving the thermal stability of ADN, thereby improving the stability of the propellant formula; the mass loss is increased by 1.34% to 8.98%, thereby promoting the complete decomposition of ADN, so that it can be more fully burned in the propellant formula. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a SEM image of ADN used in the embodiments of the present invention.
[0015] Figure 2 The thermal decomposition DSC graph (a) and TG graph (b) of ADN used in the examples of the present invention are shown.
[0016] Figure 3 is a SEM image of the SH-SiGO / ADN composite prepared in Example 1 of the present invention.
[0017] Figure 4 The thermal decomposition DSC graph (a) and TG graph (b) of the SH-SiGO / ADN composite prepared in Example 1 of the present invention.
[0018] Figure 5It is a SEM image of the graphene / ADN composite prepared in Comparative Example 1 of the present invention.
[0019] Figure 6 The thermal decomposition DSC graph (a) and TG graph (b) of the graphene / ADN composite prepared in Comparative Example 1 of the present invention are shown.
[0020] Figure 7 It is a SEM image of the reduced graphene oxide / ADN composite prepared in Comparative Example 2 of the present invention.
[0021] Figure 8 The thermal decomposition DSC graph (a) and TG graph (b) of the reduced graphene oxide / ADN composite prepared in Comparative Example 2 of the present invention are shown.
[0022] Fig. 9 It is a SEM picture of the carbon nanotube / ADN composite prepared in Comparative Example 3 of the present invention.
[0023] Fig.10 The thermal decomposition DSC graph (a) and TG graph (b) of the carbon nanotube / ADN composite prepared in Comparative Example 3 of the present invention are shown.
[0024] Fig.11 is a SEM image of the composite prepared in Comparative Example 4 of the present invention.
[0025] Fig.12 is a SEM image of the composite prepared in Comparative Example 5 of the present invention.
[0026] Fig.13 is a SEM image of the composite prepared in Comparative Example 6 of the present invention.
[0027] Fig.14 is a SEM image of the composite prepared in Comparative Example 7 of the present invention. DETAILED DESCRIPTION
[0028] Unless otherwise specified, the scientific and technical terms in this article are understood according to the knowledge of ordinary technicians in the relevant fields. It should be noted that based on the carrier preparation scheme of the present invention, those skilled in the art can optimize the methods of the present invention, including but not limited to specific reactants, ratios of reactants in each step, temperature and duration, drying temperature and calcination temperature to achieve the relevant effects of the carrier of the present invention.
[0029] The 3-mercaptopropyltriethoxysilane-modified graphene oxide used in the following examples was prepared by the method disclosed in CN202010885150.0; graphene, reduced graphene oxide and carbon nanotubes were purchased through the distributor Beijing Bailingwei Technology Co., Ltd.; ammonium dinitramide (ADN) was provided by the Xi'an Modern Chemistry Research Institute, with an impact sensitivity of 9.3 J, a friction sensitivity (66°, 2.5 MPa) of 72%, a thermal decomposition temperature of 195.07°C, and a mass loss of 83.17% in the TG test. Figure 1 and Figure 2 They are the electron microscope image, thermal decomposition DSC image and TG image of ADN respectively.
[0030] The impact sensitivity of the following examples was tested using the impact sensitivity test method in GJB770A-97; the friction sensitivity was tested using the friction sensitivity test method in GJB770A-97.
[0031] Embodiment 1:
[0032] 0.4 mg SH-SiGO was added to 20 g γ-butyrolactone and ultrasonically dispersed at 21 °C for 1 h. 0.4 g ADN was added to 14 g γ-butyrolactone and stirred at 26 °C for 12 min until ADN was completely dissolved. The SH-SiGO dispersion was poured into the ADN solution, and the system was stirred at 24 °C for 0.7 h and ultrasonically dispersed for 14 min.
[0033] The mixed solution of ADN and SH-SiGO was added dropwise to 540 g of dichloromethane under stirring at 21° C. After the addition was complete, the solution was filtered and dried at room temperature to constant weight to obtain 0.38 g of SH-SiGO / ADN composite.
[0034] According to the test, the impact sensitivity of the SH-SiGO / ADN composite prepared in this example is 10.0 J, the friction sensitivity is 20%, the thermal decomposition temperature is 198.14° C., and the mass loss after thermal decomposition is 89.22%.
[0035] Embodiment 2:
[0036] 15 mg SH-SiGO was added to 55 g γ-butyrolactone and ultrasonically dispersed at 24 °C for 1.0 h. 1.9 g ADN was added to 48 g γ-butyrolactone and stirred at 28 °C for 26 min until ADN was completely dissolved. The SH-SiGO dispersion was poured into the ADN solution, and the system was stirred at 36 °C for 0.9 h and ultrasonically dispersed for 12 min.
[0037] The mixed solution of ADN and SH-SiGO was added dropwise to 700 g of dichloromethane at 38° C. under stirring. After the addition was completed, the solution was filtered and dried at room temperature to constant weight to obtain 1.78 g of SH-SiGO / ADN composite.
[0038] According to the test, the impact sensitivity of the SH-SiGO / ADN composite prepared in this embodiment is 11.7 J, the friction sensitivity is 22%, the thermal decomposition temperature is 196.63° C., and the mass loss after thermal decomposition is 88.16%.
[0039] Embodiment 3:
[0040] Step 1, add 4.5 mg of 3-mercaptopropyltriethoxysilane modified graphene oxide (SH-SiGO) to 40 g of γ-butyrolactone, and ultrasonically disperse at 25° C. for 1.5 h; add 0.3 g of ADN to 10 g of γ-butyrolactone, stir at 25° C. for 15 min, and wait until ADN is completely dissolved; pour the SH-SiGO dispersion into the ADN solution, stir the system at 30° C. for 1 h, and ultrasonically disperse for 10 min;
[0041] Step 2, add the mixed solution of ADN and SH-SiGO obtained in step 1 dropwise into 500 g of dichloromethane under stirring at 30° C. After the addition is complete, filter the solution to collect the precipitate, and dry it at room temperature to constant weight to obtain 0.28 g of SH-SiGO / ADN composite.
[0042] After testing, the impact sensitivity of the SH-SiGO / ADN composite prepared in this example is 19.3 J, the friction sensitivity is 31%, the thermal decomposition temperature is 200.13°C, and the mass loss after thermal decomposition is 84.51%. Figure 4 shown.
[0043] Scanning electron microscopy (SEM) analysis: Figure 1 The ADN solid shown is a needle-shaped crystal, and the particles are uneven. In contrast, the SH-SiGO / ADN composite prepared in this example has a spherical structure and is relatively uniform. Figure 3 shown.
[0044] Comparative Example 1:
[0045] The difference between this comparative example and Example 3 is that SH-SiGO is replaced by graphene; the SEM analysis of the prepared composite is as follows Figure 5 As shown;
[0046] After testing, the impact sensitivity of the composite prepared in this comparative example is 9.5 J, the friction sensitivity is 72%, the thermal decomposition temperature is 195.75°C, and the thermal decomposition mass loss is 93.76%. Figure 6 shown.
[0047] Comparative Example 2:
[0048] The difference between this comparative example and Example 3 is that SH-SiGO is replaced by reduced graphene oxide; the SEM analysis of the prepared composite is as follows: Figure 7As shown; after testing, the impact sensitivity of the composite prepared in this comparative example is 9.0J, the friction sensitivity is 68%, the thermal decomposition temperature is 189.28°C, and the thermal decomposition mass loss is 92.52%, see Figure 8 shown.
[0049] Comparative Example 3:
[0050] The difference between this comparative example and Example 3 is that SH-SiGO is replaced by carbon nanotubes; the SEM analysis of the prepared composite is as follows: Fig. 9 As shown;
[0051] After testing, the impact sensitivity of the composite prepared in this comparative example is 8.0 J, the friction sensitivity is 64%, the thermal decomposition temperature is 194.55°C, and the thermal decomposition mass loss is 93.69%. Fig.10 shown.
[0052] Comparative Example 4:
[0053] The difference between this comparative example and Example 3 is that γ-butyrolactone is replaced by butyrolactone; the SEM analysis of the prepared composite is as follows: Fig.11 ;
[0054] After testing, the composite prepared in this comparative example has an impact sensitivity of 7.7 J, a friction sensitivity of 54%, a thermal decomposition temperature of 194.99° C., and a thermal decomposition mass loss of 79.04%.
[0055] Comparative Example 5:
[0056] The difference between this comparative example and Example 3 is that γ-butyrolactone is replaced by N-methylpyrrolidone; SEM analysis of the prepared composite is as follows: Fig.12 ;
[0057] According to tests, the composite prepared in this comparative example has an impact sensitivity of 6.1 J, a friction sensitivity of 60%, a thermal decomposition temperature of 195.02° C., and a thermal decomposition mass loss of 79.57%.
[0058] Comparative Example 6:
[0059] The difference between this comparative example and Example 3 is that in step 1, 4.5 mg SH-SiGO and 0.3 g ADN are added to 50 g γ-butyrolactone and stirred at 25° C. for 1 hour and 155 min. The SEM analysis of the prepared composite is as follows: Fig.13 ;
[0060] According to tests, the composite prepared in this comparative example has an impact sensitivity of 5.5 J, a friction sensitivity of 70%, a thermal decomposition temperature of 193.47° C., and a thermal decomposition mass loss of 81.17%.
[0061] Comparative Example 7:
[0062] The difference between this comparative example and Example 3 is that the dichloromethane in step 2 is replaced with 1,4-dioxane; the SEM analysis of the prepared composite is as follows: Fig.14 ;
[0063] According to tests, the composite prepared in this comparative example has an impact sensitivity of 8.9 J, a friction sensitivity of 72%, a thermal decomposition temperature of 194.88° C., and a thermal decomposition mass loss of 82.57%.
[0064] Embodiment 4:
[0065] 40 mg SH-SiGO was added to 40 g γ-butyrolactone and ultrasonically dispersed at 24 °C for 1.4 h. 2.5 g ADN was added to 45 g γ-butyrolactone and stirred at 28 °C for 25 min until ADN was completely dissolved. The SH-SiGO dispersion was poured into the ADN solution, and the system was stirred at 35 °C for 0.8 h and ultrasonically dispersed for 14 min.
[0066] The mixed solution of ADN and SH-SiGO was added dropwise to 1130 g of dichloromethane at 34° C. under stirring. After the addition was complete, the solution was filtered and dried at room temperature to constant weight to obtain 2.36 g of SH-SiGO / ADN composite.
[0067] According to the test, the impact sensitivity of the SH-SiGO / ADN composite prepared in this embodiment is 11.9 J, the friction sensitivity is 26%, the thermal decomposition temperature is 197.84° C., and the mass loss after thermal decomposition is 92.15%.
[0068] The test results of the products prepared in the above embodiments and comparative examples are shown in Table 1.
[0069] Table 1
[0070]
[0071]
Claims
1. 3-Mercaptopropyltriethoxysilane modified graphene oxide is used to reduce the impact sensitivity and friction sensitivity of ammonium dinitramide or / and improve the thermal stability and mass loss of ammonium dinitramide.
2. A method for preparing a 3-mercaptopropyltriethoxysilane-modified graphene oxide / ammonium dinitramide composite, characterized in that: The method comprises the following steps: Step 1, at 20-40° C., uniformly mix a γ-butyrolactone solution of 3-mercaptopropyltriethoxysilane-modified graphene oxide and a γ-butyrolactone solution of ADN to obtain a mixed solution; Step 2, under the condition of 20-40° C., the mixed solution obtained in step 1 is added dropwise to an organic solvent; after the addition is completed, the precipitate is collected and dried at room temperature to obtain a 3-mercaptopropyltriethoxysilane-modified graphene oxide / ammonium dinitramide complex; the organic solvent is selected from one or a mixture of two or more of dichloromethane, toluene, cyclohexane and chloroform.
3. The method for preparing the 3-mercaptopropyltriethoxysilane modified graphene oxide / ammonium dinitramide composite according to claim 2, characterized in that: Graphene oxide is added into gamma-butyrolactone, and ultrasonic dispersion is performed at a temperature of 20 to 35° C. to obtain a gamma-butyrolactone solution of graphene oxide.
4. The method for preparing the 3-mercaptopropyltriethoxysilane modified graphene oxide / ammonium dinitramide composite according to claim 2, characterized in that: Add ammonium dinitramide to γ-butyrolactone, and stir evenly at a temperature of 20-35° C. to prepare a γ-butyrolactone solution of ADN.
5. The method for preparing the 3-mercaptopropyltriethoxysilane modified graphene oxide / ammonium dinitramide composite according to claim 2, characterized in that: The γ-butyrolactone solution of 3-mercaptopropyltriethoxysilane-modified graphene oxide is added to the γ-butyrolactone solution of ADN, and the mixture is dispersed by ultrasonic after stirring at 20-35° C. to obtain the mixed solution obtained in step 1.
6. The method for preparing the 3-mercaptopropyltriethoxysilane modified graphene oxide / ammonium dinitramide composite according to claim 2, characterized in that: The amount ratio of 3-mercaptopropyltriethoxysilane modified graphene oxide and γ-butyrolactone in the γ-butyrolactone solution of 3-mercaptopropyltriethoxysilane modified graphene oxide is 0.4mg-40mg:20g-40g; the amount ratio of ADN and γ-butyrolactone in the γ-butyrolactone solution of ADN is 0.3g-2.5g:10g-50g.
7. The method for preparing the 3-mercaptopropyltriethoxysilane modified graphene oxide / ammonium dinitramide composite according to claim 6, characterized in that: The amount of organic solvent used is 500g to 1500g.
Citation Information
Patent Citations
Synthesis method of 3-mercaptopropyltriethoxysilane modified graphene oxide
CN112062784A
HMX coated with GO (graphene oxide) through electrostatic self-assembly and preparation method of HMX
CN106431792A
Synthetic method of 3-aminopropyltriethoxysilane modified graphene oxide
CN107746054A
Method for preparing graphene-coated spheroidization ammonium dinitramide
CN109574776A
Method for constructing ammonium dinitramide coating layer by adopting graphene oxide Pickering emulsion
CN109988052A